Exquisite sensitivity of the ligand field to solvation and donor polarisability in coordinatively saturated lanthanide complexes. Issue 61 (13th July 2018) - Mason, Kevin; Harnden, Alice C.; Patrick, Connor W.; Poh, Adeline W. J.; Batsanov, Andrei S.; Suturina, Elizaveta A.; Vonci, Michele; McInnes, Eric J. L.; Chilton, Nicholas F.; Parker, David
Abstract : The second coordination sphere determines ligand field in lanthanide coordination complexes. Abstract : Crystallographic, emission and NMR studies of a series of C 3 -symmetric, nine-coordinate substituted pyridyl triazacyclononane Yb(iii ) and Eu(iii ) complexes reveal the impact of local solvation and ligand dipolar polarisability on ligand field strength, leading to dramatic variations in pseudocontact NMR shifts and emission spectral profiles, giving new guidance for responsive NMR and spectral probe design.